Strategies Implemented in Teaching English for Young Learners in Primary School - Wulandari, Ni Luh Putu Titin; Ratminingsih, Ni Made; Ramendra, Dewa Putu (Journal of Education Reseach and Evaluation, 2020)
Teaching English to young learners is not an easy task. Teacher needs to use appropriate learning strategies so the students are engaged and motivated in teaching and learning process. The current study aimed at identifying the teaching English strategies used by fifth grade English teacher and the problems encountered by teacher in teaching English for young learner. This study was a descriptive qualitative research and conducted in SD Suta Dharma Denpasar Bali. In collecting the data, classroom observation and interview were conducted. The result showed that there were eight strategies applied by teacher in teaching English. They are; listen and repeat, listen and do, question and answer, in-pair, cooperative learning, and games. Furthermore, the problems experienced by teacher were lack of media of teaching English and lack of knowledge of strategy in TEYL. The problems occurred because the teacher has a limited knowledge on how to teach English for young learners and the lack of resources of teaching media available in school.